A new Scandinavian Chamaedrilus species (Clitellata: Enchytraeidae), with additional notes on others - Martinsson, Svante; Klinth, Mårten; Erséus, Christer (Zootaxa, 2018)
Chamaedrilus (earlier referred to as Cognettia) is a well-known genus of terrestrial and limnic enchytraeids, currently with 19 known species in the world. Some of its species are morphologically cryptic and can only be identified using genetic (DNA) information. Many of them reproduce asexually, and the prevalence of sexual mature individuals is generally low in the populations. Chamaedrilus asloae sp. nov. (Clitellata: Enchytraeidae) is described based on material from two rivers in Norway, one in Sweden, and from a wet deciduous forest in Denmark. With the material at hand, no morphological characters completely separate C. asloae from C. chalupskyi; none of the available specimens of the new species are sexually mature. However, four molecular markers (two mitochondrial, two nuclear) support that C. asloae is a distinct, separately evolved lineage, which is sister to a clade consisting of C. glandulosus and C. varisetosus. In this study, too, the fully developed sexual organs of C. chalupskyi and C. varisetosus are described and illustrated.